Solid state physics - Ashcroft, Neil W.; Mermin, N. David; Ashcroft, Neil W. (New Delhi, Cenage learning, 1976)
A Single introductory text presenting both aspects of the subject, descriptive and analytical. The authors of this book aim at exploring the variety of phenomena associated with the major forms of crystalline matter, while laying the foundation for a working understanding of solids through clear, detailed and elementary treatements of fundamental theoretical concepts. This book is designed for introductory courses at either the undergraduate or graduate level. Statistical mechanics and the quantum theory lie at the heart of solid state physics.
Appendix A-P, 757-798p.; Index 799-826p.
Keywords: Physics-solid state